2017
DOI: 10.1016/j.imr.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Amaranthus paniculatus Linn. ameliorates diabetes-associated complications in alloxan-induced diabetic rats

Abstract: BackgroundThe aim of this study was to evaluate the hypoglycemic, hypolipidemic, and anti-inflammatory potentials of ethanolic extract of leaves of Amaranthus paniculatus linn. (EEAP) on alloxan-induced diabetic rats scientifically. Hyperglycemia induces the generation of free radicals which can affect antioxidant defenses, thus leading to the disruption of beta cellular functions, oxidative damage to membranes, leading to the release of C-reactive protein and altered lipid metabolism.MethodsDiabetes was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Giribabu et al [ 27 ] stated that STZ-nicotinamide-induced cardiac injuries were accompanied by significant increases in troponin I and CK-MB in diabetic rats. On the contrary, TQ ameliorated the cardiac injuries that occurred in diabetic rats through hindering inflammatory progression and enhancing antioxidant status [ 28 ]. This experiment revealed that TQ potentiated the antioxidant status of plasma along with cardiac muscles of STZ-treated rats via significant decreases in plasma NO and cardiac MDA, while significantly increasing the plasma and cardiac T.SOD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giribabu et al [ 27 ] stated that STZ-nicotinamide-induced cardiac injuries were accompanied by significant increases in troponin I and CK-MB in diabetic rats. On the contrary, TQ ameliorated the cardiac injuries that occurred in diabetic rats through hindering inflammatory progression and enhancing antioxidant status [ 28 ]. This experiment revealed that TQ potentiated the antioxidant status of plasma along with cardiac muscles of STZ-treated rats via significant decreases in plasma NO and cardiac MDA, while significantly increasing the plasma and cardiac T.SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes accompanied by inflammation and heart disorder is correlated with increased inflammatory biomarkers and cytokines [ 30 ], and therefore, plasma E-selectin, CRP, and IL-6 can be augmented in diabetic rats. Nawale et al [ 28 ] stated that alloxan-induced diabetic rats had a significant level of CRP. Also, CRP, IL-6, E-selectin, and TNF- α were significantly raised in diabetic rats in response to oxidative damage [ 5 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]. Leaves were claimed for antioxidant activities, antiviral activities, especially chikungunya, and reduction of oxidative stress [13][14][15][16]. Young leaves, fruits, pods, and unripe seeds are edible and contained crude protein, ash, crude fiber, carbohydrates, amines, amides, carboxylic acids, and aromatic compounds [17].…”
Section: Introductionmentioning
confidence: 99%
“…Especially important, given the high NCD (particularly diabetes) rates in the Pacific and northern Australia, are the anti-diabetes and anti-cardiovascular disease effects of most of the plants featured in the factsheets, demonstrated in scientific studies. Studies with evidence for this include the following: drumstick [ 36 , 37 , 38 , 50 , 60 ], amaranth [ 61 , 62 , 63 ], bele [ 64 , 65 , 66 ], chilli [ 67 , 68 , 69 ], purslane [ 70 , 71 , 72 ], kangkong [ 73 , 74 , 75 ], ofenga [ 76 , 77 , 78 ], hedge panax [ 79 , 80 ], chaya [ 39 , 40 ], pumpkin [ 81 , 82 ], and choko [ 83 , 84 ]. Their inclusion in the diet in sufficient quantity is likely to reduce the risk of diabetes and cardiovascular disease, not only by reducing glycemic load when they are included with high-carbohydrate meals, but also because of specific anti-diabetes effects.…”
Section: Resultsmentioning
confidence: 99%